2015
DOI: 10.1155/2015/963816
|View full text |Cite
|
Sign up to set email alerts
|

Floristic Composition, Vegetation Structure, and Regeneration Status of Woody Plant Species of Oda Forest of Humbo Carbon Project, Wolaita, Ethiopia

Abstract: Our current study was conducted in Oda forest to explore floristic composition, vegetation structure, and regeneration of woody species in a newly established Humbo Carbon Project. In the project, the above information for sufficient conservation and management of the forest is not well documented. Data were collected in October and December 2014. Thirty-two quadrats (20 m × 20 m) lying 100 m far apart were used for shrub and tree data. In each major plot, subplots (1 m 2 ) were established at the center and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 7 publications
7
54
0
1
Order By: Relevance
“…This indicates altitude significantly influence basal area of an area. This finding was also in line with other similar report (Markos and Simon, 2015). The mean basal area for lower altitude, middle altitude and upper altitude were 6.40 m 2 /ha, 6.48 m 2 /ha and 10.15 m 2 /ha, respectively.…”
Section: Species Diversity and Evennesssupporting
confidence: 93%
See 3 more Smart Citations
“…This indicates altitude significantly influence basal area of an area. This finding was also in line with other similar report (Markos and Simon, 2015). The mean basal area for lower altitude, middle altitude and upper altitude were 6.40 m 2 /ha, 6.48 m 2 /ha and 10.15 m 2 /ha, respectively.…”
Section: Species Diversity and Evennesssupporting
confidence: 93%
“…Basal area was negatively correlated with grazing intensity and human disturbance (r = −0.3, p =0.01), and positively correlated with altitude (r = 0.44, p < 0.001) ( Table 9). Altitude and slope have an equally strong significant (p< 0.0001) effect on basal area of species (Markos and Simon, 2015). Although the linear trend explains a significant amount of the variability in basal area on the altitude gradient (Carpenter, 2005).…”
Section: Relationship Between Vegetation Patterns and Environmental Fmentioning
confidence: 95%
See 2 more Smart Citations
“…Cluster analysis of the current study showed G. nervosa is the most dominant species in the study area whereas, different ecological studies also find similar trend of results among the floral groups (Chowdhury, Islam et al, 2018;Erenso, Vegetati Marya, & Wendawek, 2014;Flinn & Lechowicz, 2008;Sajib & Uddin, 2016). In addition, the regeneration of the forest is affected not only by environmental factors but also by anthropogenic activities (De Cauwer, 2016;Kuma & Shibru, 2015). In Durgpur hill forest (DHF), some of the anthropogenic activities seriously observed during data collection e.g., introduction of alien invasive species, intentional fire, fuel wood collection, extensive litter collection were the threats to regenerating flora in the study area.…”
Section: Discussionsupporting
confidence: 65%